“ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN SINGLE INDEX MODEL PADA EMITEN YANG TERMASUK KE DALAM INDEKS LQ-45 PERIODE 2011- 2016” - Hana Tamara Putri; Santi Dwi Lestari (J-MAS (Jurnal Manajemen dan Sains), 2017)
Research portfolio optimal aims to understand return and risks portfolio, and know how much teh proportion of funds invested. The period used in this reseach was februari 2011-januari 2016. Population to research there are stock companies joined in LQ-45 index. The sample of the research are 21 sample. The data collected is secondary data. Tekhnik data analysis used in research this is the kind of index singular to know shares from portrfolio optimal. Shares who was a candidate portfolio optimal are stocks having the value ERB greater than or equal to cut off-rate. Portfolio optimal formed by the shares having value ERB more of the value of cut of rate that is 0.0031. Based on the research done showed 10 stock who was a candidat portfolio optimal from 21 sample. The propotion of funds drom 10 company is: UNVR of 31.18%, ICBP of 20.40%, GGRM of 5.84%, BBCA of 14.83%, CPIN of 5.05%, JSMR of 10.08%, LPKR of 4.82%, BBRI of 6.01%, INTP of 1.16%, dan BMRI of 0.63%. Expected return portfolio receive is 1.73% monthly with the risk 0.2%. the conclusion that obtained was that investors rational to invest the funds to into the optimal portfolio of 10 shares formed.Keyword : investation, optimal stock